STUDI TENTANG INTENSITAS SUARA DANUPAYA PENGENDALIAN KEBISINGAN DI BANDAR UDARAHUSEIN SASTRANEGARA BANDUNG TAHUN 2014 - Pradita Wira Riadiany; Sugeng Abdullah (Buletin Keslingmas, 2015)
PDAM Tirtawening Environmental Quality Control Measurement Laboratory Bandung stated thatHusein Sastranegara airport had highest noise intensity equal to 89.83 dB (A) so that the researcherwants to investigate the sound intensity and noise control in the Husein Sastranegara airport Bandung2014.The research design used was descriptive research which was intended to obtain vivid descriptionrelated sound intensity and noise control in Husein Sastranegara airport Bandung 2014 with five-pointmeasurement that describes the apron (aircraft parking space), check in / luggage space and the ticketprocess, passengers waiting room, public park, and housing.The research results shows that the sound intensity in Husein Sastranegara airport Bandungmeasurement in all locations for 83.78 dB (A) on the apron (aircraft parking area), 72.66 dB (A) at thecheck in / hall ticket and luggage process, 75.37 dB (A) in the passenger waiting room, 65.93 dB (A) atthe public parking lot and 68.52 dB (A) at the housing. The highest sound intensity results was in theapron (aircraft parking area) 85.33 dB (A) at 08:40 am.Manager of Husein Sastranegara airport Bandung expected to encourage the airports employeesto use personal protective equipment such as ear muff while on duty at the apron (aircraft parking) andconduct sound intensity measurement on a regular basis in order to recognize hazard that can interferewith employee activities.